THE EFFECT OF PROFIT PERSISTENCE AND CASH HOLDING ON PROFIT QUALITY WITH ACCOUNTING CONSERVATISM AS MODERATION - Deni Herdiansyah; Suripto; Nofryanti (ZILLZELL MEDIA PRIMA, 2024)
This study aims to examine the effect of profit persistence and cash holding on profit quality with accounting conservatism as a moderator. The research method used is an associative quantitative method. The data used in this study is panel data, which is a combination of time series data and cross section data. The population in this study is Business Index-27 companies listed on the Indonesia Stock Exchange in 2019-2023. The determination of samples by purposive sampling technique was obtained from 17 companies with 85 observation data. The analysis technique and hypothesis testing were carried out by panel data regression analysis through EViews ver-12. Based on the results of the T test, it is known that profit persistence does not have a significant effect on profit quality. On the other hand, cash holding affects the quality of profits. Meanwhile, accounting conservatism cannot moderate the influence of profit persistence variables and cash holding variables on profit quality.